The Serpent King : a Novel - Zentner, Jeff (New York : Crown Books for Young Readers, 2016)
The son of a Pentecostal preacher faces his personal demons as he and his two outcast friends try to make it through their senior year of high school in rural Forrestville, Tennessee without letting the small-town culture destroy their creative spirits and sense of self.
Keywords: Self-actualization (Psychology) -- Juvenile fiction; Friendship -- Juvenile fiction; Country life -- Juvenile fiction; Self-actualization (Psychology) -- Fiction; Friendship -- Fiction; Country life -- Fiction; Tennessee -- Juvenile fiction; Tennessee -- Fiction; Young adult fiction